2008
DOI: 10.1176/appi.ajp.2008.07091532
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype, Cortisol, and Cognitive Function in Community-Dwelling Older Adults

Abstract: Background Elevated cortisol may be a risk factor for cognitive decline in aging. Genetic factors may influence individual vulnerability to the adverse effects of stress on cognitive function in aging. Methods We investigated whether gene-environment interaction by apolipoprotein E genotype and cortisol predicted cognitive performance in an urban population of older adults. A cross-sectional analysis of data was conducted from a population-based sample of 50–70 year old men and women. Cognitive performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 45 publications
6
66
1
Order By: Relevance
“…However, the effects of APOE on cortisol levels in humans (Fiocco et al, 2008;Peskind et al, 2001) and mice (Raber et al, 2000;Reverte et al, 2014;Robertson et al, 2005;Thorngate et al, 2002) are less clear. Additionally, several studies have shown varying results when examining the relationship between APOE and cortisol on stress and cognitive function (Beluche et al, 2010;Gallagher-Thompson et al, 2001;Gerritsen et al, 2011;Lee et al, 2008). Looking beyond basal levels of cortisol, Yehuda et al (2005) showed that the normal circadian rhythm of cortisol levels is flattened in Holocaust survivors with PTSD compared with non-exposed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of APOE on cortisol levels in humans (Fiocco et al, 2008;Peskind et al, 2001) and mice (Raber et al, 2000;Reverte et al, 2014;Robertson et al, 2005;Thorngate et al, 2002) are less clear. Additionally, several studies have shown varying results when examining the relationship between APOE and cortisol on stress and cognitive function (Beluche et al, 2010;Gallagher-Thompson et al, 2001;Gerritsen et al, 2011;Lee et al, 2008). Looking beyond basal levels of cortisol, Yehuda et al (2005) showed that the normal circadian rhythm of cortisol levels is flattened in Holocaust survivors with PTSD compared with non-exposed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a limitation because previous studies have suggested the modifying role of APOE-4 on the association between cortisol levels and cognition (Gerritsen et al, 2011;Lee et al, 2008). However, recent evidence does not support the modifying role of APOE-4 in this relationship (Fiocco et al, 2008;Lara et al, 2013).…”
Section: Study Strengths and Limitationsmentioning
confidence: 93%
“…Furthermore, there are other clinical studies that examined these relationships but yielded mixed findings with most studies reporting higher morning cortisol levels. In addition, some studies focused on specific study populations, for example, among APOE-4 carriers and non-carriers (Gerritsen et al, 2011;Lara et al, 2013;Lee et al, 2008), MCI subjects (Lind et al, 2007;Venero et al, 2013), and diabetic patients (Reynolds et al, 2010). Thus, these previously mentioned studies were not generalizable to the older general population.…”
Section: Blunted Cortisol Response Is Associated With Poorer Cognitivmentioning
confidence: 99%
“…Although previous studies have demonstrated the potentiating effects of environmental stressors, such as problems meeting basic needs, on the relationship between APOE e4 and CD (Comijs, Van Den Kommer, Minnaar, Penninx, & Deeg, 2011;Lee et al, 2008;Lee, Glass, James, Bandeen-Roche, & Schwartz, 2011;SachsEricsson, Corsentino, Collins, Sawyer, & Blazer, 2010), few have examined these effects based on race. According to the 'Weathering' hypothesis suggested by Geronimus, Hicken, Keene, and Bound (2006), older African-Americans may have experienced consistently higher stress throughout their lives, causing them to be more vulnerable to later insults.…”
Section: Racementioning
confidence: 99%